Fatigue behavior of strain‐hardening cement‐based composites—From the single fiber level to real‐scale application. (7th August 2019) - Mueller, Steffen; Ranjbarian, Majid; Mechtcherine, Viktor
Abstract: Strain‐hardening cement‐based composites (SHCC) are a class of fiber‐reinforced cementitious materials, which exhibits large non‐elastic deformations and high strain capacity under tensile loading. Mix design, mechanical performance under quasi‐static and impact loading as well as durability properties of SHCC has been intensively investigated in the last two decades. Furthermore, a number of pilot and real applications in the practice of construction have been reported. However, there is still a considerable lack of knowledge regarding the behavior of material under cyclic loading. The paper at hand gives an overview of the authors work on the fatigue behavior of SHCC. Starting at the single fiber level, deterioration processes caused by different cyclic loading scenarios are presented and discussed. Next, the fatigue behavior of composite material is studied accompanied by morphological investigation of crack patterns and fracture surfaces. Finally, a practical application of SHCC in road construction is presented highlighting the advantages of using this high‐performance material.